Load balancing technique using semiconductor devices / Nor Azlan Abdul Aziz - Abdul Aziz, Nor Azlan (1992)
The objective of this project is to study feasibility of developing a new method for balancing 3 phase unbalanced load with respect to the supply system using an inverter device. This report comprise of three stages : (i) computer simulation ii) hardware design and (3) experimental research. The first staqe describes the analysis of an inverter in which the schematic configuration is simulated using Saber software.